Personality traits and severity of wife abuse among Iranian women - Motevaliyan, Seyed Mehdi; Yaacob, Siti Nor; Juhari, Rumaya; Mansor, Mariani; Baratvand, Mahmood (Canadian Center of Science and Education, 2014)
The main purpose of this study was to determine the relationships between personality traits and severity of wife abuse among Iranian women in Tehran city in Iran. The study involved 398 women who sought treatment at 4 selected hospitals by using multistage stratified sampling technique. Conflict Tactic Scale (CTS2) and Five-Factor Personality Inventory (NEO-FFI) were used to measure severity of wife abuse and personality traits respectively.Findings showed that out of 398 women studied, 42.5% received minor abuse and 43.5% received severe abuse. Severity of total wife abuse was positively related to neuroticism personality and negatively related to extraversion, agreeableness and conscientiousness. However, no significant relationship was note for total wife abuse and openness personality. The result of multinomial logistic regression indicated that neuroticism personality trait was a significant predictor of minor and severe total abuse. The results of the current study highlighted the importance of personality traits in explaining the severity of wife abuse in Tehran, Iran. Therefore, strategies to prevent and intervene cases of abuse among wives in Tehran, Iran should take into consideration individual’s personality traits.